Chapter 1 Translation Strategies in Medieval Hagiography Observations on the Slavic Reception of the Byzantine Vita of Saint Onuphrius - Åkerman Sarkisian, Karine (Taylor & Francis, 2018)
This chapter argues that certain deviations can be considered as deliberate choices on part of the medieval translator. It focuses on translation features of the Byzantine Vita of St. Onuphrius at the time of its reception by medieval Slavs. The main question that will be addressed is whether lexical discrepancies can be considered translation strategies within the transmission of this text into a new cultural context. The scribe appears to have deliberately avoided the very common place name in early Byzantine hagiography. A converse strategy in translation can be seen in the treatment of toponym Egypt in a group of manuscripts of a Bulgarian recension from the fifteenth century. The material of early hagiographic translations reveals that "conflict poles" claimed as inherent to the nature of the translation are not necessarily in opposition. Different translation strategies represented practical choices for medieval translators as they do for contemporary translators, reflecting, perhaps, the very nature of text rendering across languages and cultures.